Examining the Relationship Between Preventable Psychiatric Problems and Child Extremity Fractures - Sari, Seda Aybuke; Pazarci, Ozhan; Kilinc, Seyran; Cicek, Ayla Uzun (European Journal of Therapeutics, 2022)
Objective: Extremity fractures (EF) are among the most common causes of admission to hospitals in children. We aimed to evaluate children treated for EFs by comparing them with the control group from a psychiatric perspective. Method: Thirty-six children aged between 3 and 17 years who administered to the Orthopedics and Traumatology clinic due to EF were included in the study. 36 children of similar age and gender with the study group were included as the control group. A child psychiatrist evaluated all children included in the study. A psychiatric diagnosis interview was conducted. The parents filled out the Conner’s Parent Rating Scale-Revised Short Form (CPRS-R:S). Results: Of the cases in the patient group, 66.7% were male. The ratio of rural residents in the patient group was higher compared to the control group. The most common fracture location was lower extremity (55.6%). The most common cause of the fracture was falling (52.8%). In the patient group, the ratio of the children who had previously experienced fracture was 36.1%. Psychopathology was detected to be at a higher level in the patient group. The most common was Attention Deficiency and Hyperactivity Disorder (ADHD). Children in the patient group scored higher on the CPRS-R:S than the control group. Conclusion: Children with EF exhibited more impulsive and hyperactive behaviours than controls and had more psychopathology. For this reason, it is essential to evaluate children who apply due to fracture in terms of psychopathology.